2011
DOI: 10.2147/ijwh.s15501
|View full text |Cite
|
Sign up to set email alerts
|

Role of multidetector computed tomography (MDCT) in patients with ovarian masses

Abstract: Objective:To evaluate the diagnostic accuracy of multidetector 64-slice computed tomography (MDCT) in the diagnosis and differentiation of benign and malignant ovarian masses using histopathology and surgical findings as the gold standard.Material and methods:This study was conducted in Aga Khan University Hospital, Karachi, Pakistan. Data was reviewed retrospectively from 1 November 2008 to 12 December 2009. One hundred patients found to have ovarian masses on CT scan were included in the study. CT scan was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…The results of CT in our study compared to other studies in literature (Table 7) showed a higher sensitivity, comparable to the study by Mubarak et al 19 Although our study showed a very low specificity of 46% because of the high number of false positives which may be due to non-specific inflammatory changes within the tumour, reactive lymphadenitis appearing as enlarged lymph nodes on CT, which were reported as possible malignancy, which changes the stage of disease. And also lack of extensive retroperitoneal and paraaortic lymph node dissection also would have contributed to the low specificity.…”
supporting
confidence: 83%
“…The results of CT in our study compared to other studies in literature (Table 7) showed a higher sensitivity, comparable to the study by Mubarak et al 19 Although our study showed a very low specificity of 46% because of the high number of false positives which may be due to non-specific inflammatory changes within the tumour, reactive lymphadenitis appearing as enlarged lymph nodes on CT, which were reported as possible malignancy, which changes the stage of disease. And also lack of extensive retroperitoneal and paraaortic lymph node dissection also would have contributed to the low specificity.…”
supporting
confidence: 83%
“…Radiologic assessments help decide the surgeon about whether the therapeutic approach needs to be by a general gynaecologist in a local centre or need to be referred to a cancer centre. 16 Ultrasound is the first choice of investigation to evaluate adnexal pathologies; however, quite often it is unable to differentiate nature of the lesion and asks for further imaging. MDCT can help in characterizing masses and features pertaining to benignity and malignancy can be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…MDCT can help in characterizing masses and features pertaining to benignity and malignancy can be evaluated. 16 Mature cystic teratomas, also known as dermoids, are benign germ cell tumors most commonly seen in women of reproductive and are bilateral in 10% to 25% of cases. Although dermoids can occur at any age, but they are commonly seen at younger age group than do epithelial tumors and are the most common ovarian tumors in children.…”
Section: Discussionmentioning
confidence: 99%
“…On CT scan, masses can be characterized and features pertaining to benignity and malignancy can be observed. 21 Patients with ovarian cancer present with nonspecific symptoms. The most common symptoms reported by women with ovarian cancer are pelvic or abdominal pain; increased size of the abdomen.…”
Section: Discussionmentioning
confidence: 99%